(untitled) (Information Horizons: American Journal of Library and Information Science Innovation (2993-2777), 2023)
the entry of world countries into international relations has its own peculiarities, the study of which affects the effectiveness of the entry of enterprises and organizations in other countries into international relations. In the development of international economic monasteries, the present era also has its own peculiarities, which are influenced by economic and financial crises and are the result of globalization.